Sustainable glass-ceramic foams manufactured from waste glass bottles and bentonite. Issue 11 (1st August 2020) - Pereira da Costa, Fabiana; Rodrigues da Silva Morais, Crislene; Rodrigues, Alisson Mendes
Abstract: Glass-ceramic foams were manufactured with waste glass bottle (85.7 wt%, 87.5 wt%, and 88.9 wt%) and bentonite. The raw materials were characterized by Energy-dispersive X-ray spectroscopy (EDX) and thermal gravimetric analysis (TGA). The thermal treatment to obtain the glass-ceramic foams were conducted to eliminate the polyurethane without damaging their structure. The glass-ceramic foams sintering was performed at 750 °C, 800 °C, and 850 °C. The macro and microanalysis (optical microscopy) showed a significant porosity reduction, in the samples with higher waste glass contents. Pore closure also was found in samples sintered at 850 °C. In both cases, the pore closure resulted from melting of the glass-ceramic foam. The X-ray diffraction results show that the calcium sodium silicate (Na2 Ca3 Si6 O16 ) was the main crystalline phase. The physico-mechanical properties (linear shrinkage-LS, loss of mass on fire-LMF, water absorption-WA, apparent porosity-AP, bulk density-BD, and flexural strength- σ f ) were evaluated for glass-ceramics foams containing 85.7 wt% and 87.5 wt% of waste glass, sintered at 750 °C and 800 °C. The glass-ceramic foams sintered at 750 °C showed an average pore size of 275 μm and 330 μm, porosity of 65.1% and 39.8% and flexural strength of 0.32 MPa and 1.42 MPa for samples containing 85.7 wt% and 87.5 wt% waste glass, respectively. Already sintered foams at 800 °C, the average pore size was 283 μm and 239 μm, the porosity of 37.7% and 18.8% and the flexural strength of 1.90 MPa and 3.77 MPa for samples containing 85.7 wt% and 87.5 wt% waste glass, respectively. In general, the LMF, PA and WA values decrease with the increasing temperature, while the BD, LS, and σ f values increase with temperature.